PERSPECTIVE OF THE WORD “GOBLOK” UTTERED BY UNSCRUPULOUSPREACHERS IN TERMS OF PRAGMATICS: A FORENSIC LINGUISTIC STUDY - J. Anhar Rabi Hamsah Tis’ah (Journal of Linguistica, 2024)
This study analyzes the utterance "goblok" (stupid) expressed by a preacher to an iced tea seller in Magelang, using Searle's pragmatic theory (1969) and the forensic linguistics framework by Coulthard & Johnson (2010). Employing a qualitative descriptive method, the study found that the utterance contained expressive elements of "hatred" and declarative elements of "ostracism," potentially leading to social unrest. Grammatically, the phrase "Yok ono didol goblok" (go sell it, stupid) is contradictory, lacking literal meaning and leaning more toward emotional expression or insult. From a legal perspective, the utterance meets the criteria of a criminal act of defamation as stipulated in Article 315 of the Indonesian Penal Code (KUHP). The effects of this speech include public condemnation, sympathy for the victim, and social aid provided to the iced tea seller. This research underscores the importance of language control in public discourse to prevent public disorder and negative consequences